Patient-Oriented Eczema Measure (POEM), a core instrument to measure symptoms in clinical trials: a Harmonising Outcome Measures for Eczema (HOME) statement - Spuls, Ph.I.; Gerbens, L.A.A.; Simpson, E.; Apfelbacher, C.J.; Chalmers, J.R.; Thomas, K.S.; Prinsen, C.A.C.; Kobyletzki, L.B. von; Singh, J.A.; Williams, Hywel C.; Schmitt, J. (Wiley, 2017)
Background: The Harmonising Outcome Measures for Eczema (HOME) initiative has defined four core outcome domains for a core outcome set (COS) to be measured in all atopic eczema (AE) trials to ensure cross-trial comparison: clinical signs, symptoms, quality of life and longterm control. Objectives: The aim of this paper is to report on the consensus process that was used to select the core instrument to consistently assess symptoms in all future AE trials. Methods: Following the HOME roadmap, two systematic reviews were performed which identified three instruments that had sufficient evidence of validity, reliability, and feasibility to be considered for the final COS. Results: At the 4th international HOME meeting there was broad consensus among all stakeholders that the Patient-Oriented Eczema Measure (POEM) should be used as the core instrument (87.5% agreed, 9.4% unsure, 3.1% disagreed). Conclusions: All relevant stakeholders are encouraged to use POEM as the chosen instrument to measure the core domain of symptoms in all future AE clinical trials. Other instruments of interest can be used in addition to POEM.